2016
DOI: 10.1063/1.4942448
|View full text |Cite
|
Sign up to set email alerts
|

Instability in electromagnetically driven flows. II

Abstract: In a previous paper, we have reported numerical simulations of the MHD flow driven by a travelling magnetic field (TMF) in an annular channel, at low Reynolds number. It was shown that the stalling of such induction pump is strongly related to magnetic flux expulsion. In the present article, we show that for larger hydrodynamic Reynolds number, and with more realistic boundary conditions, this instability takes the form of a large axisymmetric vortex flow in the (r, z)-plane, in which the fluid is locally pump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Among the most important differences, one is related to the presence of inlet/outlet boundary conditions, and the other to the very large fluid Reynolds numbers involved, which implies highly turbulent flows. In a second article [16], we will therefore report numerical simulations done at larger Reynolds numbers and with more realistic axial boundary conditions. We will show how the bifurcation described here leads to inhomogeneous flows at larger fluid Reynolds number.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most important differences, one is related to the presence of inlet/outlet boundary conditions, and the other to the very large fluid Reynolds numbers involved, which implies highly turbulent flows. In a second article [16], we will therefore report numerical simulations done at larger Reynolds numbers and with more realistic axial boundary conditions. We will show how the bifurcation described here leads to inhomogeneous flows at larger fluid Reynolds number.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the velocity of the flow increases with both the magnitude of the applied field and the rotation rate of the discs. Note however that the fluid velocity is always smaller than the speed of the discs, and can be much smaller if the magnetic field is expelled outside the channel at large magnetic Reynolds number, Rm = RePm [22,23].…”
mentioning
confidence: 99%
“…However, the fluid domain in the pump was assumed as a solid, and thus, the MHD effect was ignored in the fluid domain. Gissinger et al [18,19] used the direct numerical simulation method to simulate the liquid metal driven by a travelling magnetic field in a two-dimensional channel (equivalent to the meridian plane of the flow channel of ALIP), and the flow characteristics of the liquid metal under different magnetic field conditions were studied. It is found that there are critical values for Re m and Ha.…”
Section: Introductionmentioning
confidence: 99%